PENGARUH PEMBELAJARAN IPAS MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER BERBANTUAN MEDIA POWERPOINT INTERAKTIF TERHADAP KEMAMPUAN KERJASAMA DAN HASIL BELAJAR KOGNITIF SISWA KELAS IV - Prasetyo, Mubarok Agum; Widi Winarni, Endang; Juarsa, Osa (UNIB Press, 2025)
This study aims to determine the effect of the cooperative learning model type Numbered Heads Together assisted by interactive PowerPoint media on the collaboration skills and cognitive learning outcomes. This research is a quantitative study using a quasi-experimental design. The population in this study consists of 82 fourth-grade students from MI Nurul Huda in Bengkulu. Data collection techniques in this study include documentation, observation, and tests. The test used to measure students' cognitive learning outcomes consists of 6 open-ended questions related to the subject matter of IPAS Chapter 1 on the parts of plants and their functions. Observations were conducted to assess students' collaboration skills during the discussion activities. The results of this study indicate that the average cognitive learning outcomes of students using the NHT cooperative learning model assisted by interactive PowerPoint media in IPAS learning are generally categorized as very good. The N-Gain test results from the pre-test and post-test for collaboration skills and cognitive learning outcomes fall into the high category. Based on the results and discussion, it can be concluded that there is a significant influence between collaboration skills and the cognitive learning outcomes of fourth-grade students in the IPAS subject. Additionally, the study found a significant relationship between collaboration skills and cognitive learning outcomes.